The Effect of Additional Time on the Quality of Argumentation in L2 Writing Assessment: A Mixed-methods Study. Issue 3 (27th May 2021) - Lee, Senyung; Lim, Gad S.; Basse, Rachel
ABSTRACT: This study investigated the extent to which an extended time limit in an argumentative writing test affects the quality of argumentation in L2 writing. Thirty-two adult ESL learners each wrote two essays on different prompts, one in 30 minutes and one in 45 minutes in a counter-balanced design. The 64 essays were analytically rated by four trained raters. The results show that the sub-score on argumentation as well as the overall score was significantly higher for the essays written in 45 minutes than the ones written in 30 minutes. Interviews with the raters using eight pairs of essays revealed that different features of argumentation were impacted by the additional 15 minutes, depending on the overall level of writing: addressing different sides of the issue for a high level, providing sufficient support for a middle level, and addressing the prompt for a low level. In a post-test questionnaire, a majority of learners reported that the extra 15 minutes was helpful for brainstorming and organizing ideas. Implications for the use of argumentative writing tests and improving analytical descriptors on argumentation are discussed.